Kepuasan Masyarakat terhadap Pelayanan Publik pada UPTD. Pelayanan Pajak dan Retribusi Daerah Provinsi Bali - Ni Kade Sri Purnawati; I Nyoman Sujana (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
This study aims to determine community satisfaction with public services seen from the indicators of requirements, procedures, completion time, costs/tariff, product specifications for service types, executive competence, executor behavior, complaint handling, suggestions and input, facilities and infrastructure and the overall community satisfaction index. The number of samples taken was 399 respondents with accidental sampling technique. Methods of data collection using questionnaires, interviews, and documentation. The data analysis technique uses descriptive data analysis. The results of the research show that the requirement indicators get a good category, procedure indicators get a good category, completion time indicators get a bad category, cost/tariff indicators get a good category, service type specification product indicators get a good category, executor competency indicators get a good category, indicators the behavior of the implementer is in a good category, the indicators for handling complaints, suggestions and inputs are in good categories, indicators for facilities and infrastructure are in good categories, the overall community satisfaction index is in good categories.